The mask of command - Keegan, John, 1934- (New York, N.Y., U.S.A. : Viking, 1987)
The author examines 4 very distinct leadership styles and how they reflect their times. Alexander the Great, the "Heroic" leader fighting along side his men. Wellington, the "Anti-Hero" prepared to fight but without theatrics. Ulysses S. Grant the "Unheroic" leader, considering himself no better than his men. Adolph Hitler, the "False Heroic" leader, relying on past glory and simulated heroism and directing troops from miles away.
"Elisabeth Sifton books."
Comprend un index.
Bibliogr.: p. 353-359.
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Military leadership; Wellington, Arthur Wellesley, -- Duke of, -- 1769-1852 -- Military leadership; Grant, Ulysses S. -- 1822-1885 -- Military leadership; Hitler, Adolf, -- 1889-1945 -- Military leadership; Command of troops -- History; Commandement des troupes -- Histoire